2021
DOI: 10.21608/ejp.2021.68687.1027
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of some biotic and abiotic agents to control tomato early blight disease caused by Alternaria solani

Abstract: Bacillus megaterium, Bacillus subtilis, Pseudomonas fluorescens, Trichoderma harzianum, Trichoderma album and Trichoderma viride isolates, as well as different concentrations of chemical inducers, such as chitosan and salicylic acid were evaluated against Tomato early blight, under laboratory and greenhouse conditions. Under laboratory conditions, all tested bio agents, as well as the different concentrations of the tested chemical inducers, decreased the linear growth of A. solani, as the inhibition of fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition, Khalil and Adbelghany (2021) indicated that T. harzianum was the best bioagent, which inhibited the growth of A. solani, Data of this study showed that phenol components were increased with using the biofertilizer and the bioagents more than with mineral fertilizer during the two seasons. These results are in agreement with those reported by Khalil and Adbelghany (2021) who found that treated tomato plants with the bioagents led to an increase in the total dissolved phenols in tomato leaves compared to the control. The highest significant increase in the total dissolved phenols in tomato leaves was obtained from tomato plants treated with T. harzianum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Khalil and Adbelghany (2021) indicated that T. harzianum was the best bioagent, which inhibited the growth of A. solani, Data of this study showed that phenol components were increased with using the biofertilizer and the bioagents more than with mineral fertilizer during the two seasons. These results are in agreement with those reported by Khalil and Adbelghany (2021) who found that treated tomato plants with the bioagents led to an increase in the total dissolved phenols in tomato leaves compared to the control. The highest significant increase in the total dissolved phenols in tomato leaves was obtained from tomato plants treated with T. harzianum.…”
Section: Discussionsupporting
confidence: 93%
“…Agricultural fungicides combat plant pathogens: but they have negative effects on the beneficial natural organisms. Therefore, it is necessary to develop environmentally friendly and biodegradable agricultural alternatives in order to control plant pathogens (Khalil and Adbelghany, 2021). So, the use of bioagents has become important as an alternative to fungicides to prevent postharvest losses in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Each washing was performed for 15 min at 4 • C for the removal of the unreactive fixatives. Then, the sections were dehydrated for 20 min in each graded series of ethanol (30,50,70,90,95, and 100%). The sections were dried at critical point drying and then mounted on an aluminum stub with carbon tape.…”
Section: Scanning Electron Microscope (Sem) Analysismentioning
confidence: 99%
“…Effective root colonization aids microbes in inducing ISR efficiently and, thus, help them to render pathogens, including those that infect plants at spatially different locations [17,[22][23][24]. Trichoderma, Pseudomonas, Bacillus, and arbuscular mycorrhizal fungi (AMF) are some microbial isolates that have the potential to abridge plant stress [12,19,[25][26][27][28][29][30]. For instance, the application of compost containing Bacillus subtilis QST713 and Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%